Does a balance deficit persist in Australian football players with previous lower limb ligament injury? - Hrysomallis, C.; McLaughlin, P.; Goodman, C. (Journal of Science and Medicine in Sport, 2005)
A history of lower limb ligament injury is a commonly-cited risk factor for another similar injury. During the acute phase of injury, there is a balancing skill deficit in the injured limb. It has been unclear as to whether this deficit persists in the medium-to-long term for previously injured Australian footballers, contributing to the risk of re-injury. This study compared the balance ability of footballers with and without previous lower limb ligament injury and, for previously injured players, the balance ability of the previously injured limb to the opposite uninjured limb. A total of 216 players from 6 teams from the Australian Football League were tested. The balance task comprised stepping on to a foam mat on top of a force plate and maintaining one-legged balance. The subjects were divided into 4 groups based on their injury history: all ankle injuries to only one limb, recent ankle injuries to only one limb (within the last 12 months), knee ligament injury only to one limb, and no previous ankle or knee ligament injury. Statistical analysis revealed that there was no significant difference between the balance scores of any of the previously injured players and those with no previous lower limb ligament injury. There was no significant difference between the balance score of the previously injured limb with the opposite uninjured limb. It appears that a balance deficit does not persist in Australian Football players with previous lower limb ligament injury.